Century islamic education learning model: Characteristics and implications for grade iv students at SDN 03 East Pontianak - Sri Herlina; Wahab; Syamsul Kurniawan; Sahrani (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to describe the 21st Century Islamic Education Learning Model: Characteristics and Implications for Grade IV Students of SDN 03 East Pontianak. This research combines two types of research at once, namely library research and field research. The library study was conducted by collecting data from various sources such as libraries, readings, and notes. These sources include articles, books, and other relevant sources. Field research was conducted by collecting data directly in the field using observation, interview, and documentation techniques. The results showed that the characteristics of the 21st century PAI learning model and its implications for grade IV students of SDN 03 East Pontianak are that students can improve skills in critical thinking, problem solving, communication skills, collaboration, innovation and creation related to 21st century demands in PAI and students can understand, live, and practice PAI well, happily and quickly. A generation that is faithful and devoted to God Almighty and proficient in using digital technology is born. Students can adapt to the rapid changes and developments in technology.